Comprehensive analysis of m6A RNA methylation modification patterns and the immune microenvironment in osteoarthritis - Liu, Zhixin; Liu, Heng; Li, Deqiang; Ma, Liang; Lu, Tongxin; Sun, Hao; Zhang, Yuankai; Yang, Hui (Frontiers in Immunology, 2023)
Background: Osteoarthritis (OA) is the most common joint degenerative disease, and so far, there is no effective therapy to prevent or delay its development. Considerable attention is now being given to the impact of m6A RNA methylation modification on the disease immune regulation. However, much remains unknown about the function of m6A modification in OA. Methods: A total of 63 OA and 59 healthy samples were applied to comprehensively examine the m6A regulators mediated RNA methylation modification pattern in OA, and evaluate the impacts of distinct patterns on the characteristics of OA immune microenvironment, including immune infiltration cells, immune responses and human leukocyte antigen (HLAs) genes expression. In addition, we screened out the m6A phenotype-related genes and further explored their potential biological functions. At last, we verified the expression of key m6A regulators and their associations with immune cells, in vitro. Results: Most of m6A regulators was differentially expressed in OA samples compared to the normal tissues. Based on six hub-m6A regulators identified as abnormally expressed in OA samples, we developed a classifier to distinguish OA patients from healthy individuals. We noted that immune characteristics of OA were correlated with m6A regulators. For instance, YTHDF2 had a strongest significantly positive correlation with regulatory T cells (Tregs) and IGFBP2 was strongest negatively associated with dendritic cells (DCs), which were confirmed by the immunohistochemistry (IHC) staining. Two distinct m6A modification patterns were determined: pattern B had higher infiltrating immunocytes and more active immune responses than pattern A, and two patterns differed in the expression of HLA genes. We also identified 1,592 m6A phenotype-related genes that could mediate the OA synovitis and cartilage degradation by the PI3K-Akt signaling pathway. Quantitative real-time polymerase chain reaction (qRT-PCR) results indicated that IGFBP2 was significantly overexpressed, while YTHDF2 mRNA expression was decreased in OA samples, which was consistent with our findings. Conclusion: Our research proves the essential impact of m6A RNA methylation modification on the OA immune microenvironment, and helps to explain the regulatory mechanism behind it, which may open up a new direction for more precise immunotherapy of osteoarthritis.